Association of living arrangements with all-cause mortality among older adults: a propensity score-matched cohort study - Lining Pu; Jingni Zhang; Xiaoxue He; Degong Pan; Huihui Wang; Xue Zhang; Xian Sun; Xiaojuan Liu; Shulan He; Jiangping Li (BMC, 2023)
Abstract Background Many studies exist on the living arrangements and health status of older adults, but the findings have been inconsistent. Therefore, we examined the relationship between living arrangements and all-cause mortality in older adults. Methods This perspective study was based on the Chinese Longitudinal Healthy Longevity Survey (CLHLS) from 2011 to 2018. We used a sample aged 65 years and over included in the study in 2011. Propensity score matching was performed to minimize bias and Cox proportional hazards regression models were conducted. Results A total of 7,963 participants were included. Of these, 1,383 were living alone, 6,424 were living with families, and 156 were living in nursing homes. In the propensity score-matched cohort, older adults living alone had a significantly lower risk of all-cause mortality than those living with families (hazard ratio 0.85; 95% confidence intervals 0.76 to 0.95). Living alone was prominently associated with a decline in mortality compared with living in nursing homes (hazard ratio 0.61; 95% confidence intervals 0.44 to 0.84). There was no significant difference in mortality between living in nursing homes and living with families (hazard ratio 1.19; 95% confidence intervals 0.89 to 1.60). Subgroup analyses indicated that there was no significant interaction with age, sex, education, or residence. Conclusions The risk of all-cause mortality was significantly lower in older adults living alone than in those living with families or living in nursing homes. This article's findings suggest the need to adopt multiple approaches to meet the needs of senior care services.